2002
DOI: 10.1111/1475-679x.00038
|View full text |Cite
|
Sign up to set email alerts
|

GAAP versus The Street: An Empirical Assessment of Two Alternative Definitions of Earnings

Abstract: Managers, security analysts, investors, and the press rely increasingly on modified definitions of GAAP net income, known by such names as “operating” and “pro forma” earnings. We document this phenomenon and discuss competing explanations for the recent rise in the use of such modified earnings numbers and implications for the interpretation of related accounting research. Our results show that over the past 20 years there has been a dramatic increase in the frequency and magnitude of cases where “GAAP” and “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
492
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(559 citation statements)
references
References 15 publications
39
492
1
9
Order By: Relevance
“…Furthermore, analysts assign a higher rating to a firm with higher earnings from its core business operations. This result corresponds with the finding of Bradshaw and Sloan (2002), who found that "street earning" (Note 3) reflects a firm's earnings per share reported on a "continued operations" basis. Hanna (2001) explored the effect of special items on analysts' earnings forecasts and indicated an increasing error in analysts' forecasts when special items exist.…”
Section: Firm Characteristics For Herdingsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, analysts assign a higher rating to a firm with higher earnings from its core business operations. This result corresponds with the finding of Bradshaw and Sloan (2002), who found that "street earning" (Note 3) reflects a firm's earnings per share reported on a "continued operations" basis. Hanna (2001) explored the effect of special items on analysts' earnings forecasts and indicated an increasing error in analysts' forecasts when special items exist.…”
Section: Firm Characteristics For Herdingsupporting
confidence: 89%
“…Note 3. Bradshaw and Sloan (2002) defined "street earnings" as "the numbers announced by corporations in their press releases and tracked by analyst estimate clearinghouse services, such as I/B/E/S, Zacks, and First…”
mentioning
confidence: 99%
“…The view that earnings are more value-relevant than operating cash flow has recently been contested by others who claim that the earnings quality has decreased in recent years (Francis & Schipper 1999;Bradshaw & Sloan 2002, Hodge 2003. Moreover, the literature suggests that the higher value-relevance of earnings compared to cash flow might vary with industry affiliation (see e.g.…”
Section: Furthermorementioning
confidence: 99%
“…Prior research finds that street earnings are more value-relevant to investors than GAAP operating earnings (Bradshaw and Sloan 2002). This result is intuitive because street earnings remove the transitory components of earnings (which are not very useful in predicting future earnings) and capture an earnings number that is predictive of future earnings (Francis et al 1996;Ramakrishnan and Thomas 1998 Brown and Sivakumar (2003) find that investors use street earnings in equity valuation to a larger extent than Compustat's version of core earnings, suggesting that street earnings should be the number on which managers focus if they are interested in favorable valuations of their stocks.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Analyst forecast tracking services, such as I/B/E/S and First Call, exclude certain earnings components in calculating a firm's ''core earnings'' and this core earnings measure is often referred to as ''street earnings. '' 1 Prior research suggests that (1) investors react more to street earnings than to GAAP earnings and (2) investors extrapolate current performance into sustainable future earnings, making street earnings more relevant for equity valuation than other versions of core earnings (Bradshaw and Sloan 2002;Brown and Sivakumar 2003;Frankel and Roychowdhury 2005). Despite the apparent importance of street earnings to investors, the process by which the composition of street earnings is determined is poorly understood.…”
Section: Introductionmentioning
confidence: 99%